2022
DOI: 10.1038/s41390-022-02164-y
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental consequences of early plasma sodium changes in very preterm infants

Abstract: Background Sodium fluctuations in very preterm neonates and their neurodevelopmental consequences are not well described. Methods We assessed the changes in plasma sodium and glucose in the first days of life in very preterm neonates and studied the association of glucose-corrected plasma sodium fluctuations on neurodevelopmental outcomes. We included 147 consecutive neonates born before 29 weeks of gestation in our center and retrospectively obtained plasma sodium, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…The importance of sodium homeostasis in optimizing additional outcomes of preterm infants has been highlighted by other investigators. Both hyper-and hyponatremia in the first week of postnatal life have been associated with increased mortality, risk of intraventricular hemorrhage, and neurodevelopmental impairment, [32][33][34][35] Interestingly, children born prematurely and supplemented to sodium intakes of 4-5 mEq/kg/d for days 4-14 of postnatal life had significantly improved neurodevelopmental performance (motor function, performance IQ, the general memory index) at 10-13 years of age compared to infants receiving 1-1.5 mEq/kg/d. 36 Whether the potential effects of sodium on neurocognitive development and brain growth are separate from those on somatic growth is not known.…”
Section: Does Sodium Supplementation Results In Improved Postnatal Gr...mentioning
confidence: 99%
“…The importance of sodium homeostasis in optimizing additional outcomes of preterm infants has been highlighted by other investigators. Both hyper-and hyponatremia in the first week of postnatal life have been associated with increased mortality, risk of intraventricular hemorrhage, and neurodevelopmental impairment, [32][33][34][35] Interestingly, children born prematurely and supplemented to sodium intakes of 4-5 mEq/kg/d for days 4-14 of postnatal life had significantly improved neurodevelopmental performance (motor function, performance IQ, the general memory index) at 10-13 years of age compared to infants receiving 1-1.5 mEq/kg/d. 36 Whether the potential effects of sodium on neurocognitive development and brain growth are separate from those on somatic growth is not known.…”
Section: Does Sodium Supplementation Results In Improved Postnatal Gr...mentioning
confidence: 99%
“…Briefly, all individuals born preterm at any of the three main neonatal intensive care units in Montreal between 1987 and 1996 were eligible. The following outcomes were available for all participants: neonatal complications, follow‐up evaluation, presence of cerebral palsy, anthropometric measures, blood pressure, pulmonary function tests, oral glucose challenge and lipid profile, as previously described 5,12–14 . The presence of criteria for hypertension, adiposity, airflow limitation and glucose intolerance were noted, 11 and a count of those adverse outcomes (range 0–4) was used to reflect the health condition of each participant.…”
Section: Methodsmentioning
confidence: 99%
“…The following outcomes were available for all participants: neonatal complications, follow-up evaluation, presence of cerebral palsy, anthropometric measures, blood pressure, pulmonary function tests, oral glucose challenge and lipid profile, as previously described. 5,[12][13][14] The presence of criteria for hypertension, adiposity, airflow limitation and…”
Section: Study Populationmentioning
confidence: 99%
“…These variables were selected because of their known association with alterations in serum sodium values, GA [ 26 ], SGA [ 27 ], urine output [ 5 ], daily fluid intake [ 28 ], and glucose values [ 29 ] or likelihood of reflecting higher severity of illness (i.e., vasopressor use). Previous research has shown associations of neonatal outcomes and sex, with male infants having higher rates of mortality and respiratory comorbidities; therefore, we included sex as a potential confounder [ 30 ].…”
Section: Methodsmentioning
confidence: 99%